Lactate Arterial-Central Venous Gradient among COVID-19 Patients in ICU: A Potential Tool in the Clinical Practice. (25th September 2020) - Nardi, Giuseppe; Sanson, Gianfranco; Tassinari, Lucia; Guiotto, Giovanna; Potalivo, Antonella; Montomoli, Jonathan; Schiraldi, Fernando
Abstract : Objective . In physiological conditions, arterial blood lactate concentration is equal to or lower than central venous blood lactate concentration. A reversal in this rate (i.e., higher lactate concentration in central venous blood), which could reflect a derangement in the mitochondrial metabolism of lung cells induced by inflammation, has been previously reported in patients with ARDS but has been never explored in COVID-19 patients. The aim of this study was to explore if the COVID-19-induced lung cell damage was mirrored by an arterial lactatemia higher than the central venous one; then if the administration of anti-inflammatory therapy (i.e., canakinumab 300 mg subcutaneous) could normalize such abnormal lactate a-cv difference. Methods . A prospective cohort study was conducted, started on March 25, 2020, for a duration of 10 days, enrolling 21 patients affected by severe COVID-19 pneumonia undergoing mechanical ventilation consecutively admitted to the ICU of the Rimini Hospital, Italy. Arterial and central venous blood samples were contemporarily collected to calculate the difference between arterial and central venous lactate (Delta a-cv lactate) concentrations within 24 h from tracheal intubation ( T 0 ) and 24 hours after canakinumab administration ( T 1 ). Results . At T 0, 19 of 21 (90.5%) patients showed a pathologic Delta a-cv lactate (median 0.15 mmol/L; IQR 0.07–0.25). In the 13 patients undergoing canakinumab administration, at T 1, Delta a-cv lactate decreased in 92.3% of cases, the decrease being statistically significant ( T 0 : median 0.24, IQR 0.09–0.31 mmol/L; T 1 : median −0.01, IQR −0.08–0.04 mmol/L; p = 0.002 ). Conclusion . A reversed Delta a-cv lactate might be interpreted as one of the effects of COVID-19-related cytokine storm, which could reflect a derangement in the mitochondrial metabolism of lung cells induced by severe inflammation or other uncoupling mediators. In addition, Delta a-cv lactate decrease might also reflect the anti-inflammatory activity of canakinumab. Our preliminary findings need to be confirmed by larger outcome studies.